A Feasibility Study of using Cosmic Ray Muons to Monitor Supercritical CO2 Migration in Geological Formations. (August 2015) - Zhong, Jinjin; Yi, Jianxin; Xie, Qiyuan; Jiang, Xi
Abstract: In geological carbon dioxide (CO2 ) storage, possible leakage of supercritical CO2 from underground storage is one of the main threats to defeat the climate goals of carbon sequestration. A feasibility study of using cosmic ray muons to monitor supercritical CO2 migration in geological formations is carried out in this study, which is focused on improving theaccuracy of numericalsimulation. In the simulation, during the process of supercritical CO2 migrating underground, both change in the density and the material composition of the underground storage were taken into consideration. A model of promising underground storage sites was established. Propagation of cosmic ray muons in the underground storage model was investigated by Monte Carlo simulation. The results showed that this method could detect 5% change in the supercritical CO2 volume fraction in the storage model at depths of about 1 km. This was deduced by investigating the sensitivity of the number of the cosmic ray muons penetrating the storage model to the change inside the model, which in practical case, was caused by CO2 migration inside the underground storage.